Mixed phenotype acute leukemia, the dissection of an enigmatic disease in the era of novel therapies - Karasek, Magdalena; Kubiszewska, Izabela; Sobas, Marta (Frontiers in Pediatrics, 2025)
BackgroundMixed-phenotype acute leukemia (MPAL) is a rare and heterogeneous subtype of acute leukemia, associated with unfavorable outcomes. MPAL is defined by the presence of more than 20% blasts and bi- or trilineage assignment based on strong immunophenotypic markers, with specific subcategories characterized by BCR::ABL1, KMT2A, ZNF384, or BCL11B rearrangements. This review aims to summarize current knowledge and challenges in the diagnosis and management of MPAL.MethodsData were synthesized primarily from meta-analyses and original studies, with a particular emphasis on the roles of immunophenotyping, cytogenetics, and novel targeted therapies from 1985 to the present.ResultsMPAL accounts for 1%–5% of acute leukemias, with B/myeloid (59%) and T/myeloid (35%) subtypes being the most prevalent. Cytogenetic abnormalities are identified in up to 90% of cases, predominantly complex karyotypes. Molecular investigations have identified frequent mutations in genes such as RUNX1, DNMT3A, IDH1/2, NOTCH1, and FLT3, particularly enriched in T/myeloid MPAL. Adverse prognostic factors include KMT2Ar, elevated leukocyte counts, extramedullary disease, and bilineage disease biology. Generally, the prognosis for adults is poorer than for the pediatric population. No standardized treatment strategy has been established. Retrospective analyses indicate superior complete remission rates and overall survival with ALL-based regimens, and allogeneic hematopoietic stem cell transplantation remains crucial for improving survival. Recently, hybrid regimens such as FLAG-IDA and CLAG-M have demonstrated promising efficacy with acceptable toxicity. Targeted therapies are emerging options, although lineage switch under selective therapeutic pressure remains a concern.ConclusionsMPAL remains a significant challenge in diagnosis and treatment. Advances in molecular characterization have enhanced classification techniques and have the potential to inform personalized treatment strategies. Considering the rarity and heterogeneity of MPAL, extensive prospective multicenter trials are imperative to develop evidence-based therapeutic protocols.